Leaf anatomy of cultivated vine plants in cultivation environments and altitude regions - Carneiro Gabardo, Gentil; dos Santos, Keli Cristina; Fenili, Cristhian Leonardo; Bueno, Jessica; Silveira Vargas, Rafaela; Pereira, Jomar (Scientia Agraria Paranaensis, 2021)
Plants can develop anatomical variations depending on the cultivation environment, and such characteristics can influence their physiology and significantly alter their capacity. The aim of the study was to evaluate the anatomical characteristics of the leaves of ‘Niágara Rosada’ grape varieties grown in different growing environments and different regions in the 2019/20 production cycle. An experiment was carried out in three cultivation conditions (full sun, under canvas and under plastic) in the region of Lages-SC. Another test was conducted in orchards with crops under full sun, in the regions of Lages-SC and Caçador-SC, altitudes of 1100 and 900 m, respectively. The variables analyzed were: stomatal density and stoma size, plant production and average cluster mass and chlorophyll index. In the first experiment, higher stomatal density was observed in plants grown in full sun compared to plants under canvas and greater stomatal area in plants grown under plastic in relation to the other conditions. The chlorophyll index was higher in plants grown under canvas, with no differences for plants grown under plastic. Plants grown under plastic showed higher production and average mass of clusters compared to plants grown under canvas and full sun. The stomatal density of vines produced in Caçador is higher than vines produced in Lages. The cultivation of vines under plastic cover is very advantageous in several aspects, such as: increased production and also protects against natural events, such as hail.